1968
DOI: 10.1099/00221287-50-3-399
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Maintenance Energy and Growth Rate on the Metabolic Activity, Morphology and Conidiation of Penicillium chrysogenum

Abstract: The rates of utilization of energy-yielding substrates (glucose and oxygen) by Penicillium chrysogenum in glucose-limited chemostat cultures were resolved into requirements or 'rations' for growth and maintenance. The maintenance ration of glucose was almost all oxidized to carbon dioxide. Over the growth rate range 0.023-0.075 hr-l only vegetative growth occurred; although the filamentous growth form predominated, the occurrence of pellets and swollen organisms increased with growth rate. At growth rates of 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
60
1
1

Year Published

1973
1973
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 212 publications
(72 citation statements)
references
References 20 publications
10
60
1
1
Order By: Relevance
“…During subaerial growth, A. niger produces chains of black spores from biseriate conidiophores (55), but like other molds (15,16,56,62) it also conidiates in submerged culture in response to severe nitrogen or carbon limitation (15, 27, 46). More recent molecular studies…”
mentioning
confidence: 99%
“…During subaerial growth, A. niger produces chains of black spores from biseriate conidiophores (55), but like other molds (15,16,56,62) it also conidiates in submerged culture in response to severe nitrogen or carbon limitation (15, 27, 46). More recent molecular studies…”
mentioning
confidence: 99%
“…Darlington (1964) and Johnson (1964) demonstrated that 100 grams of biomass from hydrocarbon requires approximately three times the amount of oxygen to produce the same amount of biomass from carbohydrate. Later, product formation as well as biomass production by oxygen conversion was calculated (Righelato et al, 1968, Cooney 1979.…”
Section: Oxygen Requirements Of Fermentationsmentioning
confidence: 99%
“…At least ten pieces of mycelium were measured for each estimate of hyphal growth unit. Chemostat cultures were operated by using the medium and conditions described previously (Righelato et al 1968).…”
Section: Measurement Of Growth Rate and Branching In Shakeflasksmentioning
confidence: 99%
“…The simple medium was that of Righelato, Trinci, Pirt & Peat (1968) containing 30 g glucose/l. For submerged cultures I 5 ml portions were dispensed in IOO ml conical flasks.…”
mentioning
confidence: 99%